Obtenção de levoglucosan a partir de pirólise - Oliveira, Bianca Aparecida Meneghel de (2017)
Due to the great need of the use of polymers and the impacts caused to the environment through its production and its use it becomes feasible to study ways of seeking to produce bioplastics. Biodegradable polymeric materials do not harm the environment and its degradation process occurs through the use of such material as a source of nutrients for bacteria, fungi or algae, more efficient than conventional plastics. It is known that levoglucosan has as potential to manufacture biopolymers. Therefore, the present work sought to identify the most efficient way to obtain this material through the pyrolysis of sugarcane straw, for which the parameters temperature and rotation speed were evaluated. In addition, the absence and presence of acid treatment in the biomass, through an experimental planning. In order to analyze the characteristics of the biomass the immediate analysis was carried out. From the experimental design the best results for pyrolysis were the tests with temperature 1 and velocity 1, without acid treatment, but it was not possible to perform the same analyzes for acid treatment, due to inconsistent results. Using Thin Layer Chromatography it was possible to detect the presence of the compound of interest for the dilution of the bio-oil in methanol (1:25) for the tests 2 and 6 and for the concentrated bio-oil it was possible to detect the presence of levoglucosan for It was not possible to quantify for which of the tests the highest incidence of the compound occurred, but it can be deduced from the staining that the tests 2 and 6 for the same conditions of speed and temperature presented the best results . Although it was possible to identify levoglucosan, to assert the most efficient way to obtain it and use it for polymer production, it would be necessary to perform the quantification through techniques such as FT-IV, CG / MS or HPLC.